Assessment of ultrabasic rock and volcanic tuff for the treatment of acid mine drainage - Joyce Kristy Primus (2016)
Metal-rich acid mine drainages (AMD) need to be treated appropriately prior to final discharge into the surrounding environment. In this study, the feasibility of using ultra basic rock (UBR) and volcanic tuff (VT) as treatment materials to remove heavy metals from AMD was investigated. Initially, the efficacy of the materials were tested using acidic aqueous metal solutions (pH=2.5; metal concentration; 10 mg/L) at different contact time, particle size and solid-solution ratio. Subsequently the materials were tested using AMD samples collected from Mamut Copper Mine pit. The initial and final metal concentrations (Cu, Fe, Mn and Zn) and final pH were the main parameters analysed. The results shows that the metal removal from aqueous solutions by both materials s dependant on contact time, particle size and solid solution ratio. The highest efficiency was achieved at 12 hours and 16 hours contact time (for UBR and VT respectively), particle size <0.5 mm and solid solution ratio 0.06 g/MI. Under this condition, the removal of Cu, Fe, Mn and Zn by UBR is 100, 100, 71 and 96%, respectively, while by VT is less efficient at 74, 91, 36 and 52%, respectively. The efficiency of UBR is closely associated with the ability of the material to increase the pH of solution (and the final pH attained) and subsequent precipitation of the metals. By contract, metal removal by VT is more likely associate with adsorption. When tested on AMD samples (at optimum condition), UBR resulted In 100, 100, 67 and 99% removal of Cu, Fe, Mn and Zn, respectively from mine pit sample and 90, 97,6 and 69%, respectively, from Nasapang drain sample. Comparatively, VT resulted in 96, 100, 67 and 92% respectively; from mine pit sample and 60, 98, 12 and 11%, respectively, from Nasapang drain sample. While the efficiency of either material is dependent on the AMD sample, the efficiency of VT is lower than UBR and has relatively greater potential compared to VT as treatment material for removal of heavy metals from AMD.